MASALAH SISWA UNDERACHIEVER DAN PERAN GURU BIMBINGAN DAN KONSELING DALAM PENGENTASANNYA - Lelono, Setyo (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2011)
The aim of the research is to disclose some aspects of underachiever students and the role of guidance teachers in handling the students problems. This study is classified into descriptive quantitative method. The underachiever studentâ€™s problems based upon each problemed field ranked from the most problems up to the least problems namely: (1) learning skill problems, (2) personal problems, 3) learning environment and socio-emotional problems, (4) lesson material mastery pre requirement problems and (5) medium of learning problems. Most of the underachiever student eventually have less learning motivation. The parents of underachiever student who are most of strata 1 graduates and civil servants. The role of guidance and counseling teacher is not yet optimal and not yet focus because they have no time for entering classes and theÂ  ratio number of the guidance and counseling teacher is not equal with the number of the guided students.